PERAN GURU PPKN DALAM MENGEMBANGKAN KEDISIPLINAN PESERTA DIDIK SMA TAMAN MULIA KUBURAYA PADA PEMBELAJARAN DARING - Riani, Devia; Rustiyarso, Rustiyarso; Purnama, Shilmy; Aminuyati,, Aminuyati; Syamsuri, Syamsuri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This study aims to determine, "The Role of Civics Teachers in Developing Discipline of Taman Mulia Kuburaya High School Students in Online Learning". This study used a qualitative approach, with subjects namely, PPKn teachers, vice-students, counseling teachers, and male and female SMA Taman Mulia class XII IPS 1 students as a sample because at the time the research was conducted the students who came to school only totaling 5 people. Data collection techniques using the method of observation, interviews, and documentation. While the data collection tools used are interview guides, observation guidelines and documentation tools. Data analysis techniques are data collection, data reduction, data presentation, and drawing conclusions. The validity checking technique uses source triangulation and technical triangulation, time triangulation. The results of the study show the discipline of students in online learning, namely, students often do not submit assignments, are late for class, do not attend class, and often do not fill in attendance. The role of Civics teachers in developing student discipline in online learning, namely, the teacher as a guide, the teacher as a role model, and the teacher as a motivator. The obstacles faced by PPKn teachers in developing student discipline are factors from themselves, factors from the environment where they live, and family factors. Efforts made by PPKn teachers to overcome student discipline barriers in online learning, namely: guiding and advising students and communicating well with students